Creating Public Value through innovation (E-government) and improvement: Case study of the South African Social Security Agency (SASSA) Alice Office, Eastern Cape. - Muzamhindo, Spiwe (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.